ANTIOXIDANT ACTIVITY OF YELLOW PUMPKIN NOODLES (Cucurbita moschata Durch) WITH TUNA BONE MEAL - Leffy Hermalena; Hafiva Reski Oktavia; Eddwina Aidila Fitria (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2023)
Lash yellow is one of the alternative ingredients for making dry noodle products substituted with wheat flour. The use of yellow pumpkin in making dry noodles because yellow pumpkin contains lots of carbohydrates, vitamins, and fiber. In addition to substituting yellow pumpkin, noodles can also add nutrients that are not yet present in the basic composition, namely calcium, obtained from the by-products of fish bones. The purpose of this study was to determine the effect of adding tuna bone meal on the characteristics and antioxidant activity of yellow pumpkin noodles and to find out the addition of the best tuna bone meal to produce yellow pumpkin noodles that panelists liked. The observational data were analyzed using ANOVA and Duncan's New Multiple Range Test (DNMRT) at a level of 1%. The treatment in this study was the addition of tuna bone meal (A = 2%, B = 6%, C = 10%, D = 14%, E = 18%). It turns out that the addition of tuna bone meal has a very real effect on water content, ash content, protein content, antioxidant activity, and calcium levels. All treatments meet the quality requirements of dry noodles SNI 8217-2015. Based on organoleptic tests, the best treatment is treatment A with the addition of tuna bone meal as much as 2% with an average of 5.39 organoleptic, with a moisture content value of 11.71%, ash content of 0.12%, protein content of 14.64%, antioxidant activity of 22.00% and calcium content of 18.8 mg / 100g.